Self-Help: Extrajudicial Rights, Privileges and Remedies in Contemporary American Society - Brandon, Douglas I. (1984)
This Special Project examines the myriad forms of self-help currently available to persons in American society. It groups and discusses notable self-help rights, privileges, and remedies under topical classifications that parallel traditional jurisprudential categories. Parts H through VI of the Special Project sketch the legally fashioned contours and explore the legal, social, and political consequences of self-help methods in tort law, criminal law and law enforcement, commercial transactions, landlord-tenant relations,and family law matters. Part VII explores the attorney's role in the development and implementation of curative self-help procedures such as mediation. Special Project concludes by examining the function, mechanisms, and merits of two increasingly popular alternative dispute resolution processes--rent-a-judge programs and the ombudsman--that offer hope for continued peaceable dispute resolution